Praktik Sarapan pada Orang Dewasa Indonesia: Perbedaan Perkotaan dan Pedesaan dan Faktor yang Berkaitan: Breakfast Practices Among Indonesian Adults: Urban and Rural Differences and Its Associated Factors - Arifa, Vina Hasna; Wiradnyani, Luh Ade Ari; Khusun, Helda; Februhartanty, Judhiastuty (Universitas Airlangga, 2024)
Backgrounds: Adults in Indonesia have challenges due to the high prevalence of obesity. Factors that contributed to obesity included unhealthy eating practices. Skipping breakfast habits are linked to health issues such as non-communicable diseases (NCDs). Breakfast practices also reflected the social and cultural dynamics in urban and rural. Socioeconomic and demographic factors could cause differences in breakfast practices between urban and rural areas in Indonesia. Objectives: This research aimed to examine the differences in breakfast practices among Indonesian adults in urban and rural areas based on various characteristics and to explore the association between socioeconomic and demographic characteristics with breakfast practices. Methods: This was a cross-sectional study using secondary data from the Indonesia Food Barometer (IFB) in 2018. A total of 770 adults (26–45 years old) were examined to observe the differences in breakfast practices (skipping breakfast, eating together, buying food, cooking food, and activities during meals) in urban and rural areas. Logistic regression analysis was also employed to examine the association between skipping breakfast and modern breakfast practices with socioeconomic and demographic variables. Results: Chi-square analysis showed significant differences between urban and rural areas in eating alone, eating outside the home, and buying food during breakfast (p-value <0.001). Factors related to skipping breakfast were education level and type of residence (all p-value <0.001), while occupation (p-value = 0.004) and type of residence (p-value <0.001) were related to modern breakfast practices. Conclusions: There were differences in breakfast practices between urban and rural. Skipping breakfast and modern breakfast practices were more prevalent in urban areas.